The research of Mongolian smes human resource recruitment and selection in some problem - E, Zolzaya; Hong, Zhou Xiao (Proceedings of the Mongolian Academy of Sciences, 2018)
SMEs are the growth engine of the many countries economy and currently two thirds of the workforce work in this sector. They are also a good source of job creation, with positive hiring intentions. Intensive and supportive of SMEs and policy development remains the priority of the world’s economics. Development of SMEs plays an important role in economic growth while reducing poverty and unemployment. In addition, SME development contributes to a reduction in inequitable income distribution, support social stability, and private sector development. Today, small and medium-sized businesses (SMEs) are middle-class societies, which are the basis of sustainable economic development of many countries. In developed countries 70-90 percent of the total industries account for small and medium sized enterprises (SMEs). The present study sought to investigate the recruitment and selection practices of Small and Medium Enterprises (SMEs) in Mongolia. The research contributes to indicate that an understanding and adoption of formal and context specific aspects of recruitment and selection practices by owner/managers will help position the SME’s at the forefront of socio-economic development. A major limitation of the study was a lack of current data on the addresses and locations of SMEs’ as well as inadequate information to enhance easy classification and access. The present research contributes to knowledge by bringing to the fore specific and contextual issues that may influence recruitment and selection practices of SMEs.